Agricultural Technology Implementation in Corn Plants in Gorontalo Regency - Rahmat Yahya; Syilvia Syam; Rahmadanih (Journal of Public Administration and Government, 2022)
This study is part of Gorontalo Regency's corn crop food security initiatives using agricultural technology. The purpose of this study was to determine the effect of a 50 EC neem spray on insect population, attack intensity, cob weight without cob, cob length, and cob diameter of corn planted using the 2:1 legowo planting technique. This study was place in the cornfields of Dumati Village, Telaga Biru District, Gorontalo Regency, and lasted 5 months, from March to July 2021. This is a quantitative study that used a Randomized Block Design (RBD) with different doses of neem seed oil 50 EC: control (no treatment), neem seed oil 10 ml/1liter water, neem seed oil 15 ml/1liter water, and neem seed oil 20 ml/1liter water. The results revealed that applying 50 EC neem seed oil had a substantial influence on Spodoptera frugiperda pest population at 28 DAP, 35 DAP, and 42 DAP, as well as the severity of Spodoptera frugiperda pest attack at 35 DAP and 42 DAP. The length of the corn cob is the same. However, it had no effect on the weight of the cob without the husks or the diameter of the corn cob. However, in terms of yield of cob weight without husks and corn cob diameter, neem seed oil treatment with a dosage of 20 ml/1liter of water was the best treatment.